The impact of livestock asset transfers on the livelihoods of the ultra-poor. Issue 8 (17th November 2022) - Das, Narayan; Kamruzzaman, Md.; Ahmed, Md. Shakil
ABSTRACT: This paper estimates the impacts of Livestock Asset Transfers on the livelihoods of the ultra-poor in West Bengal, India. The programme provides the female members of ultra-poor households with livestock assets as grants. We find that the intervention increases per capita monthly income by Rs 1061 (122% increase). It also increases the food expenditures of households and enables them to secure enough food to eat at least two meals a day. Furthermore, the programme also increases the number/amount of owned livestock assets, poultry, and cultivable lands amid the treatment households.